PEMBELAJARAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SEKOLAH MENENGAH PERTAMA - Mawardani, Windi (Universitas Negeri Makassar, 2020)
Learning to Write Description Texts in Grade VII Middle School Students. This study aims to: (1) describe the learning of writing descriptive text by grade VII teachers of SMP Negeri 2 Wonomulyo, and (2) describing the learning of writing descriptive text by grade VII A students of SMP Negeri 2 Wonomulyo. This research is a qualitative descriptive study. Data collection is done by observation, documentation, and interviews. The results of this study indicate that learning activities undertaken by teachers include learning planning, learning implementation, and learning assessment. Meanwhile, learning activities undertaken by students relate to the implementation of learning that produces products in the form of written text descriptions.